Optimizing Talent Development for Goalkeepers: Psychological Characteristics, Stressors, and Sustainable Pathways in Elite Soccer - Camille Sabourin; Eric Terrien; Denis Ha (Current Issues in Sport Science)
Introduction Research on talent identification and development has grown significantly, driven by increasing interest from practitioners aiming to optimize these processes in applied settings. However, several challenges persist, including issues such as early selection biases, relative age effects, maturity-related inequalities, language barriers, and the underrepresentation of specific groups, such as female players, para-football athletes, and goalkeepers (Kelly, 2024). Goalkeepers occupy a unique and essential role within soccer teams, requiring specialized training to meet and sustain the demands of elite performance and development (e.g., Otte et al., 2022). The position’s requirements differ fundamentally from those of outfield players, resulting in distinctive developmental pathways and psychological profiles. For instance, goalkeepers face unique challenges, including the need to maintain concentration despite fluctuations in activity, make split-second decisions under pressure, and manage stress during high-stakes moments (e.g., penalty shootouts; Otte et al., 2020; de Castro et al., 2021). Despite their importance, research on the talent development of goalkeepers remains sparse. Therefore, given these gaps, the present study aimed to examine the psychological characteristics and stressors encountered by goalkeepers at various stages of their progression toward elite performance.